2022
DOI: 10.1101/2022.05.09.491199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A histone deacetylase network regulates epigenetic reprogramming and viral silencing in HIV infected cells

Abstract: Approximately 70% of the HIV-1 latent reservoir originates from infections of CD4 T cells that occur in the months near the time of ART initiation, raising the possibility that interventions during this period might prevent reservoir seeding and reduce reservoir size. We identify class 1 histone deacetylase inhibitors (HDACi) as potent agents of latency prevention. Inhibiting HDACs in productively infected cells caused extended maintenance of HIV expression and this activity was associated with persistently el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 119 publications
(169 reference statements)
0
12
0
Order By: Relevance
“…We then infected the EPZ-719 exposed cells or control vehicle exposed cells with a GFP expressing clone of HIV (HIV-drEGFP). This specific clone contains a short half-life GFP (dreGFP) within the envelope open reading frame, allowing dynamic analysis of LTR-driven HIV expression [17]. When we measured productive HIV infection (%GFP+) by flow cytometry at 3dpi, we observed similar levels of overall infection (29% vs 26%) for EPZ-719 treated cells and cells treated with control vehicle (DMSO) respectively ( Figure 2B, 2C ).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…We then infected the EPZ-719 exposed cells or control vehicle exposed cells with a GFP expressing clone of HIV (HIV-drEGFP). This specific clone contains a short half-life GFP (dreGFP) within the envelope open reading frame, allowing dynamic analysis of LTR-driven HIV expression [17]. When we measured productive HIV infection (%GFP+) by flow cytometry at 3dpi, we observed similar levels of overall infection (29% vs 26%) for EPZ-719 treated cells and cells treated with control vehicle (DMSO) respectively ( Figure 2B, 2C ).…”
Section: Resultsmentioning
confidence: 70%
“…HIV latency is a stable and heritable phenomenon, consistent with the notion of an epigenetic program that regulates HIV latency [16]. In particular, removal of activating marks such as H3K9ac and H3K27ac by class 1 histone deacetylases (HDACs) and the addition of repressive H3K9me3 and H3K27me3 marks by histone methyltransferases have been shown to contribute to HIV latency [1719]. ATACseq analysis has also shown that latent proviruses exhibit a “closed” chromatin conformation that likely restricts access by key TFs and RNA Polymerase II (RNAPol2) [16].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In an interesting new development, Peterson et al used combinations of HDAC3-directed PROTAC and CRISPR-Cas9 knockout experiments. They showed that while either HDAC1/2 or HDAC3 targeting can prevent latency, all three enzymes must be targeted to achieve latency reversal [ 30 ▪▪ ]. Latency prevention is associated with increased H3K9ac at the proviral LTR promoter region and decreased H3K9me3, emphasizing an unexpected role of H3K9 modifications in the establishment of latency.…”
Section: Epigenetic Control Of Hiv-1 Latencymentioning
confidence: 99%